Islam and tattooing: an old question, a new research topic - Göran Larsson (Scripta Instituti Donneriani Aboensis, 2011)
Most Muslim theologians have argued on the basis of the ḥadīth-literature that tattooing is ḥarām (forbidden), but it is nonetheless possible to find both historical and contemporary examples indicating that, at different times and in different places, this art was practiced by certain Islamic groups. With specific reference to washm,or tattooing, it has been well documented that certain Muslim groups (e.g., the Berbers and the Bedouins) in places such as Africa, Syria, Saudi Arabia, Iran and West Pakistan have used tattoos for beautification, prophylaxis and the prevention of disease. Among Islam’s lay populations, tattooing has been considered significant as a healing practice for a very long time despite the formal opinions of Islamic scholars and theologians. And while in more recent times these Muslim groups appear to have abandoned past notions about the function of tattoos, which had caused a certain waning of the practice, of late it has had a resurgence—although for reasons that differ from those of distant times. The rise of interest in tattoos among Muslims has been directly observed by a handful of contemporary researchers, and is indirectly indicated by the fact that many contemporary Muslim authorities have expressed growing concern about the practice.This development has been further spurred on by the fact that many Muslims are actively seeking advice and clarification about where Islam stands on the matter of tattoos. The aim of of this article is to sketch the background of the more formal theological discussion on tattooing (especially in the ḥadīth-literature). It also aims to examine a number of contemporary religious texts that specifically deal with Muslim theological opinions about this practice: what is considered to be the problem; and what types of arguments are employed by the selected theologians in their attempts to provide answers. Is it possible to see the renewed interest in tattoos as an example of the fact that there is a gap between theory (what the theologians say) and practice (what the believers actually do)?